Aplicação do processo de eletrocoagulação no tratamento de efluentes da indústria têxtil - Souza, Paula Cristina de (2016)
This work had the objective of evaluation by physicochemical parameters of treatment methods of textile effluents by electrocoagulation, developing an integrated system of treatment of the effluent using the process of coagulation/flocculation with the electrocoagulation, using the natural cogulant/flocculant tannin and the chemical coagulants aluminium sulfate and aluminium polychloride. Therefore the physicochemical characterization of the textile effluent was accomplished in an industrial laundry in the region of Campo Mourão - Paraná studying the efficiency of coagulation/flocculation and electrocoagulation techniques to reduce the defile loads of the effluent. The best operating conditions were determined for the process of coagulation/flocculation and using laboratory-scale reactors, the operating parameters of the electrocoagulation process were optimized. In the sequence, an integrated system into the processes of coagulation/flocculation and electrocoagulation was developed. The main results of the process of electrocoagulation were obtained at a time of 30 minutes of electrolysis reaching the values of reduction of DQO of 50,66% (236,09 mg O2.L-1) for the effluent in natura and of 47,35 % (90,24mg O2.L-1) for the filtrated effluent. The experiments with the integrated processes were accomplished using the coagulation/flocculation in the best operating conditions, with the three studied coagulants, applied as pretreatment of the effluent and sequentially the electrocoagulation, also in the best operating conditions. In this case the PAC promoted the reduction of the real color of 68,11%, apparent color 82,62 %, turbidity 75,11%, real turbidity 90,15%, DQO 52,73% ( 118,82mg O2.L-1) and DQO of the filtrated effluent 53,29% (70,73 mg O2.L-1). With the aluminium sulfate the values of percentage of the real color reached 75,77%, of the apparent color 77,65%, turbidity 52,42%, real turbidity 90,16%, DQO 78,89% (64,40 mg O2.L-1) and DQO of the filtrated 64,09% ( 54,38 mg O2.L-1). For the Tannin was observed a reduction of the real color of 84,84%, apparent color 65,10%, turbidity 52,42%, real turbidity 90,53%, DQO 65,88% (102,92 mg O2.L-1) and DQO of the filtrated 54,88% (74,48 mg O2.L-1). For the DQO occurred an increase in the efficiency of the integrated treatments, in relation to the electrocoagulation process. The process of coagulation/flocculation did not demonstrate reductions in the concentrations of metal, since the integrated processes demonstrated a reduction in the concentrations of calcium and sodium. The test of toxicity obtained for the specie Lactuca sativa, demonstrated that the effluent obtained from the electrocoagulation is the most lethal for the studied specie, the electrocoagulation highlights, mainly in the highest concentrations, for presenting the highest percentiles of relative growing inhibition of the root and radicle, proving therefore toxic effect of these effluents. For the color and the DQO the values obtained for the effluent treated by the integrated processes using the coagulation/flocculation as pretreatment of the electrocoagulation with the three coagulants, the results are within the legal limits for draining in the receiving bodies.